Pengaruh Citra Tubuh terhadap Budaya Konsumsi pada Perempuan - Nafi Ibdiyana Musyarrifani (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
Women view their bodies more negatively than men and this affects their body image. Body image is a person's evaluation of his physical appearance, other people's perceptions of his body, and how his body is adapted to these perceptions. This paper will focus on discussing the arguments about how women's body image affects their consumption culture. The research method used is literature study of secondary data from book sources, online journal articles, and data published on the internet. It was found that the construction of the ideal body in society was shaped by the capitalist popular culture industry and supported by the mass media. This construction creates a standardization of the definition of ideal beauty. Not only that, the patriarchal culture that places women as symbols of beauty that fulfills aesthetic functions in the household also influences their consumption culture. In addition to being the market object of capitalism's products, women are also the main consumers of products that are believed to help increase satisfaction with their body image, such as beauty, fitness, health, and fashion products.